DUKUNGAN SOSIAL EMOSIONAL SESAMA ANGGOTA KOMUNITAS CRAFTER “DEMEN HANDMADE” - Nailufar, Nabilla Tusifa; Syadeli Hanafi; Dadan Darmawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
A community serves as a platform for members to share common interests, within which there are very strong bonds. Based on these bonds, emotional social support emerges to help ensure the well-being of its members. The “Demen Handmade” crafters’ community also plays a role in bringing together individuals with a passion for handicrafts to collaborate and share social and emotional support. Using qualitative methods, it was found that the emotional support observed manifests directly through three main forms: the giving of attention, an attitude of care, and expressions of empathy, all channelled through handicraft activities. These forms are present and provided directly between members, which in turn successfully creates a sense of comfort and acceptance within the community. This emotional support also highlights the strong sense of togetherness within the “Demen Handmade” Crafter Community. This sense of comfort and security stems from the community’s responsive nature, thereby creating an environment that supports the development of every member.